Franco : A Personal and Political Biography - Payne, Stanley G.; Palacios, Jesús, 1952- (Book collections on Project MUSE., 2014)
Built upon archival sources recently made available at the National Francisco Franco Foundation and the authors' extensive interviews with the general's daughter, Carmen Franco Polo, this new biography adds an intimate glimpse into Franco's personal and family life to the extant historiography of Franco's military career and the political machinations of his regime. Many negative portrayals of the dictator already exist. The authors successfully take great pains to be objective and balanced as they simultaneously eschew writing a hagiography of Franco and situating his seizure of the state within the context of interwar chaos and violence.